Pemanfaatan Literasi Digital Alternatif Dalam Mencegah Hoax dan Penyebarannya Bagi Pelajar Yayasan Rukun Isteri Sejahtera - Eni Heni Hermaliani; Lindung Parningotan Manik; Yan Rianto; Ferda Ernawan; , Alda Zevana Putri Widodo; , Nurul Jannah Salsabila (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Rukun Istri Sejahtera Foundation is a foundation engaged in social, educational, religious and humanitarian fields. The easy access to the internet and social media by many people, especially among students, has a bad influence as a negative effect of utilizing these innovations. More and more fake news that is often referred to as hoaxes can be accepted by the public, especially in the use of social media. In accessing digital media, you may encounter inappropriate things such as news and hoax information. Thus, students are very interested in acting out digital literacy in preventing hoaxes, including parents, teachers and all policymakers The problem that has been faced by partners is the difficulty in providing direction to students fostered by partners regarding the use of digital literacy as an alternative in preventing hoaxes and their spread. The solution for partners in overcoming these problems is to provide counseling on the use of digital literacy to prevent hoaxes and their spread to partner-assisted students. Based on these problems, this community service activity aims to develop knowledge and insights by providing counseling on the use of alternative digital literacy in preventing hoaxes and their spread to students of the Rukun Istri Sejahtera Foundation.